The Spine Vertebral Bodies 3D Modeling and its Biomechanical Advantages - Saveh, Amirhossein; Zali, Alireza; Ashrafi, Farzad; Shahzadi, Sohrab; Seddighi, Afsoun; Momenzadeh, Sirous; Behnam, Behdad; Dehpour, Omid; Chizari, Mahmoud; Gammada, Kazuyoshi (International Clinical Neuroscience Journal, 2015)
To perform an accurate approach to the spine specially for fracture stabilization a 3D model of spine surgical region may improve this mechanism and it can help the surgeon to have a deeper glance to this scenario. The pre-op planning facility is another advantage of the patient spine specific model to take a chance of making guides to direct pedicle screws safely and increase the pathomechanics of volumes of interest stability factor parallel with its mobility restoration. There are some algorithms for making 3D-reconstruction from CT or MR data-set but the main goal of in-vivo component 3D making is right component extraction from its peripheral segments to achieve the best judgment especially about the surgical approach. Here is a cervical vertebral bodies segmentation and 3D-reconstruction of two cervical adjacent levels combined with the registration process that is shown the intervertebral degree regarding to range of motion percent.